2003
DOI: 10.1097/01.ogx.0000074099.38382.13
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Main Outcomes in Breast Cancer Prevention Trials

Abstract: This study was conducted to investigate the risk factors associated with peripartum hysterectomy in women who had either vaginal or cesarean delivery. The study subjects were women (n ϭ 101) who had a peripartum hysterectomy at the authors' institution from January 1986 to April 2001. Seventy-two of the 101 patients had delivered at Yonsei University Medical Center and 29 were referred from other hospitals. Of the total 31,044 deliveries at Yonsei during this time period, 11,924 were performed by cesarean sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
208
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(226 citation statements)
references
References 0 publications
10
208
0
8
Order By: Relevance
“…A number of trials have now shown that endocrine agents such as tamoxifen (TAM) or raloxifene can prevent breast cancer in women at increased risk of the disease (Cuzick et al, 2003). The question arises as to whether agents such as these can be used for prevention specifically in women bearing BRCA1 or BRCA2 mutations.…”
mentioning
confidence: 99%
“…A number of trials have now shown that endocrine agents such as tamoxifen (TAM) or raloxifene can prevent breast cancer in women at increased risk of the disease (Cuzick et al, 2003). The question arises as to whether agents such as these can be used for prevention specifically in women bearing BRCA1 or BRCA2 mutations.…”
mentioning
confidence: 99%
“…About 5 -10% of all breast cancer cases occur in women with a strong family history, and in the Netherlands approximately 25% of these cases may be attributed to the BRCA1 and BRCA2 breast cancer susceptibility gene mutations . Several strategies to reduce the risk of breast cancer or breast cancer death may be discussed with BRCA 1/2 mutation carriers and women with a strong family history, such as intensive surveillance, chemoprevention (Cuzick et al, 2003) and prophylactic mastectomy . Guidelines for surveillance of these women mostly consist of biannual clinical breast examination (CBE), annual mammography and recommendation for monthly breast self-examination (BSE) (Vasen et al, 1998).…”
mentioning
confidence: 99%
“…Indeed, the fact that tamoxifen is cheap and accessible to under-funded healthcare systems worldwide means that this form of targeted therapy continues to save lives. However, unlike the targeted therapies of today that usually have a single anticancer application, tamoxifen became the gold standard for the targeted therapy of all stages of breast cancer (including male breast cancer), the treatment of ductal carcinoma in situ (69), a pioneering agent for the chemoprevention of breast cancer in high risk women (45,70,71) and the lead compound for the new drug group, the SERMs (72-76).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the fact that tamoxifen is cheap and accessible to under-funded healthcare systems worldwide means that this form of targeted therapy continues to save lives. However, unlike the targeted therapies of today that usually have a single anticancer application, tamoxifen became the gold standard for the targeted therapy of all stages of breast cancer (including male breast cancer), the treatment of ductal carcinoma in situ (69), a pioneering agent for the chemoprevention of breast cancer in high risk women (45,70,71) and the lead compound for the new drug group, the SERMs (72-76).The extensive laboratory studies of tamoxifen and the related nonsteroidal antioestrogen LY156,758 (keoxifene) undertaken as a prelude to initiating major trials in breast cancer prevention, described the pharmacology of SERMs that switch on and switch off target sites throughout the body. As an example of the immediate translation of the discovery of SERM action, tamoxifen was noted to block breast cancer growth but enhances the growth of endometrial cancer growth under laboratory conditions (77).…”
mentioning
confidence: 99%